2023
DOI: 10.1111/ppl.14107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus deficiency alters root length, acid phosphatase activity, organic acids, and metabolites in root exudates of soybean cultivars

Tantriani,
Weiguo Cheng,
Akira Oikawa
et al.

Abstract: Phosphorus (P) deficiency alters the root morphological and physiological traits of plants. This study investigates how soybean cultivars with varying low‐P tolerance values respond to different P levels in hydroponic culture by assessing alterations in root length, acid phosphatase activity, organic acid exudation, and metabolites in root exudates. Three low‐P‐tolerant cultivars (‘Maetsue,’ ‘Kurotome,’ and ‘Fukuyutaka’) and three low‐P‐sensitive cultivars (‘Ihhon,’ ‘Chizuka,’ and ‘Komuta’) were grown under 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…Phosphorus deficiency results in reduced plant biomass, as evidenced by declines in both shoot and root dry weights ( Tantriani et al, 2023 ). Consistent with these findings, our results indicated that shoot and root dry weight decreased significantly under treatments with insoluble P but increased following inoculation with T. viride .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus deficiency results in reduced plant biomass, as evidenced by declines in both shoot and root dry weights ( Tantriani et al, 2023 ). Consistent with these findings, our results indicated that shoot and root dry weight decreased significantly under treatments with insoluble P but increased following inoculation with T. viride .…”
Section: Discussionmentioning
confidence: 99%